Contract renegotiation by an Italian wastewater utility: Action research to promote effective tariff revision. (October 2017) - Guerrini, A.; Romano, G.
Abstract: This article focuses on the process of contract renegotiation by an Italian wastewater utility, commenced with the goal of tariff revision. The main aim of this paper is to identify the conditions that lead to contract renegotiation. It also develops new tools and operations that can facilitate this process. We utilized the action research method that involves organizations in changing situations supported by professional researchers who assume the role of change agents. The study provides some interesting insights on contract management and renegotiation, and highlights conditions that lead to the failure of contract-based regulation. Highlights: The incompleteness of contracts determines the risk of default of one of the counterparts. Concession contracts without an active role for a regulatory agency have a high rate of collapse. The lack of clear rules for tariff estimation generates information asymmetries. The ambiguity in the tariff method has weakened the wholesalers. The process of renegotiation is helped by the involvement of an independent actor.